A qualitative comparison of healthcare practitioners’ perceptions regarding fatigue as a symptom in neurological conditions: insights from a tertiary care center in Saudi Arabia - Alotaibi, Madawi; Subramanian, Murali P.; Alahmari, Wafa; Alqabbani, Samiah; Algabbani, Maha; Almuwais, Afrah (Frontiers in Rehabilitation Sciences, 2025)
IntroductionFatigue as a symptom severely affects individuals with neurological diseases, but its understanding and management remain limited, especially in the unique healthcare context of Saudi Arabia. While it has been extensively studied in stroke, its manifestations in neurological conditions and the perceptions of health professionals have not been thoroughly explored in this specific setting. Given the profound impact of fatigue on patient outcomes, understanding the attitudes of health professionals is crucial to identifying targeted interventions and significantly improving patient care in Saudi Arabia.MethodsThis qualitative study, conducted in collaboration with a diverse group of Saudi healthcare professionals, used Semi-structured interviews to explore their perspectives on fatigue in neurological diseases. The 24 participants included physiatrists, occupational therapists, and physiotherapists, all of whom played a crucial role in treating and managing individuals with neurological conditions. Semi-structured interviews were conducted in Arabic and translated into English. Data analysis involved thematic analysis using NVivo software, with themes identified iteratively until data saturation was achieved.ResultsThree overarching themes emerged from the data analysis. (1) “Fatigue is a common symptom of a neurological disorder” highlights clinicians’ recognition of the prevalence and manifestations of fatigue in various neurological disorders. (2) “Adaptive fatigue management” emphasizes the importance of individual strategies for managing fatigue, including improving endurance and environmental adaptation, and emphasizes the relationship. (3) “Fatigue and Other Conditions” explored the complex relationship between fatigue and other common neurological conditions, such as multiple sclerosis and traumatic brain injury.ConclusionThe study provides useful information about Saudi healthcare professionals’ perceptions of fatigue in neurological illnesses. Key findings stress the significance of fatigue and the need for unique designs to manage its diverse forms. While admitting limitations such as limited generalizability and inherent biases, the study advances our understanding of fatigue management in Saudi Arabia. It advocates the development of targeted therapies to improve patient care and outcomes in neurological illnesses.